2011
DOI: 10.1002/cphc.201100542
|View full text |Cite
|
Sign up to set email alerts
|

Substituent Effects on Non‐Covalent Interactions with Aromatic Rings: Insights from Computational Chemistry

Abstract: Non-covalent interactions with aromatic rings pervade modern chemical research. The strength and orientation of these interactions can be tuned and controlled through substituent effects. Computational studies of model complexes have provided a detailed understanding of the origin and nature of these substituent effects, and pinpointed flaws in entrenched models of these interactions in the literature. Here, we provide a brief review of efforts over the last decade to unravel the origin of substituent effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
105
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(113 citation statements)
references
References 215 publications
(102 reference statements)
8
105
0
Order By: Relevance
“…The benzene pair geometry in Table 1 is the parallel-displaced configuration. These studies also indicate that substituents, typically make the stacking stronger with respect to benzene stacking, which is confirmed in our results for methyl and chlorine substituents [44][45][46].…”
Section: Guest-guest Interactions In Gas Phasesupporting
confidence: 90%
“…The benzene pair geometry in Table 1 is the parallel-displaced configuration. These studies also indicate that substituents, typically make the stacking stronger with respect to benzene stacking, which is confirmed in our results for methyl and chlorine substituents [44][45][46].…”
Section: Guest-guest Interactions In Gas Phasesupporting
confidence: 90%
“…These results in relation to substituent effects on binding energies are in good agreement with results of Sherrill et al [58][59][60] and Wheeler et al [61][62][63]. Interactions for all substituted benzene dimers in comparison with the unsubstituted case enhanced.…”
Section: Resultssupporting
confidence: 91%
“…These results lead to the conclusion that the gel formation is largely dictated by the position and nature of the substituents, rather than being dominated by the quinoxalinone framework. 32, 33 Solubility and Dissolution Parameters. We previously reported that gelators exhibit (on average) higher dissolution enthalpies (ΔH diss ) and entropies (ΔS diss ) than nongelators.…”
Section: ■ Results and Discussionmentioning
confidence: 99%